Incidence and relative risk for developing cancers in women with gestational diabetes mellitus: a nationwide cohort study in Taiwan. Issue 2 (21st February 2019) - Peng, Yun-Shing; Lin, Jr-Rung; Cheng, Bi-Hua; Ho, Cheng; Lin, Yung-Hsiang; Shen, Chien-Hen; Tsai, Ming-Hung
Abstract : Objectives: To evaluate the risk of developing cancers, particularly site-specific cancers, in women with gestational diabetes mellitus (GDM) in Taiwan. Setting: The National Health Insurance Research Database (NHIRD) of Taiwan. Participants: This study was conducted using the nationwide data from 2000 to 2013. In total, 1 466 596 pregnant women with admission for delivery were identified. Subjects with GDM consisted of 47 373 women, while the non-exposed group consisted of 943 199 women without GDM. The participants were followed from the delivery date to the diagnosis of cancer, death, the last medical claim or the end of follow-up (31 December 2013), whichever came first. Primary outcome measures: Patients with a new diagnosis of cancer (International Classification of Diseases, ninth edition, with clinical modification (ICD-9-CM codes 140–208)) recorded in NHIRD were identified. The risk of 11 major cancer types was assessed, including cancers of head and neck, digestive organs, lung and bronchus, bone and connective tissue, skin, breast, genital organs, urinary system, brain, thyroid gland and haematological system. Results: The rates of developing cancers were significantly higher in women with GDM compared with the non-GDM group (2.24% vs 1.96%; p<0.001). After adjusting for maternal age at delivery and comorbidities, women with GDM had increased risk of cancers, including cancers of nasopharynx (adjusted HR, 1.739; 95 % CI, 1.400 to 2.161; p<0.0001), kidney (AHR, 2.169; 95 % CI, 1.428 to 3.293; p=0.0003), lung and bronchus (AHR, 1.372; 95 % CI, 1.044 to 1.803; p=0.0231), breast (AHR, 1.234; 95% CI, 1.093 to 1.393; p=0.007) and thyroid gland (AHR, 1.389; 95 % CI, 1.121 to 1.721; p=0.0026). Conclusion: Women with GDM have a higher risk of developing cancers. Cancer screening is warranted in women with GDM. Future research should be aimed at establishing whether this association is causal.